Gambaran Penyesuaian Diri Remaja yang Diasuh oleh Orangtua Single Mother dan Single Father - Rila Rahma Mulyani; Wike Puspita Belni; Sonia Andini (Universitas PGRI SUMATERA BARAT, 2020)
ABSTRACT This research is motivated by the existence of adolescents who are cared for by single parents who have poor communication with peers, feel inferior and often daydream, like to be alone and not open. The purpose of this study is to describe the adjustment of adolescents who are cared for by: 1) single mothers and 2) single fathers. This type of research is a descriptive qualitative type of research. The number of research informants was determined using a purposive sampling technique, amounting to 4 people, 2 teenagers from a single mother and 2 teenagers from a single father. Data collection techniques using interviews and data analysis techniques through three stages, namely data reduction, data presentation, and drawing conclusions. The results showed that: 1) adolescents who were cared for by single mather parents felt inferior and jealous of friends who had whole families, and often compared them to their family conditions, and when they had problems they preferred to be alone and did not want to share with others. 2) Meanwhile, adolescents who are cared for by single father parents show that teenagers are still unable to solve problems with their peers, such as showing their anger if their desires are not fulfilled and prefer to leave the house if advised by their parents, and do not want to listen to other people's opinions. Keyword :Adjustment, Adolescent, Single Mother, Single Father ABSTRAKPenelitian ini dilatarbelakangi oleh adanya remaja yang di asuh oleh orangtua tidak utuh yang memiliki komunikasi kurang baik dengan teman sebaya, merasa minder dan sering melamun, suka menyendiri dan tidak terbuka. Tujuan penelitian ini untuk menggambarkan penyesuaian diri remaja yang di asuh oleh: 1) orangtua single mother dan 2) orangtua single father. Jenis penelitian ini merupakan penelitian kualitatif tipe deskriptif. Jumlah informan penelitian ditetapkan dengan menggunakan teknik purposive sampling yang berjumlah 4 orang, 2 remaja dari single mother dan 2 remaja dari single father. Teknik pengumpulan data menggunakan wawancara dan teknik analisis data melalui tiga tahap yaitu reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa: 1) Remaja yang diasuh oleh orangtua single mather merasa minder dan cemburu terhadap teman yang memiliki keluarga utuh, dan sering membandingkannya dengan keadaan keluarganya, dan ketika punya masalah lebih memilih menyendiri dan tidak mau berbagi dengan orang lain. 2) Remaja yang diasuh oleh orangtua single father menunjukkan bahwa remaja masih belum mampu menyelesaikan masalah dengan teman sebaya seperti menunjukkan kemarahannya jika keinginannya tidak terpenuhi dan lebih memilih keluar rumah jika dinasehati oleh orangtua, serta tidak mau mendengarkan pendapat orang lain. Kata Kunci : Penyesuaian diri, Remaja, Single Mother, Single Father